2015
DOI: 10.1371/journal.pone.0141593
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion Behaviour of Silica Nanoparticles in Biological Media and Its Influence on Cellular Uptake

Abstract: Given the increasing variety of manufactured nanomaterials, suitable, robust, standardized in vitro screening methods are needed to study the mechanisms by which they can interact with biological systems. The in vitro evaluation of interactions of nanoparticles (NPs) with living cells is challenging due to the complex behaviour of NPs, which may involve dissolution, aggregation, sedimentation and formation of a protein corona. These variable parameters have an influence on the surface properties and the stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 46 publications
6
39
0
Order By: Relevance
“…This can be attributed to the interaction of cationic AuNP with the negative surface charge on MDA MB 231 cells. Similar results have been reported in case of silica nanoparticles, wherein, it was observed that presence of cells changes the dispersion state of nanoparticle suspension 29 . The PCS and LDV analysis to estimate size and zeta potential of these agglomerates could not be performed as the protein content of media was very high and it caused a significant interference ( Figure 6A).…”
Section: Resultssupporting
confidence: 88%
“…This can be attributed to the interaction of cationic AuNP with the negative surface charge on MDA MB 231 cells. Similar results have been reported in case of silica nanoparticles, wherein, it was observed that presence of cells changes the dispersion state of nanoparticle suspension 29 . The PCS and LDV analysis to estimate size and zeta potential of these agglomerates could not be performed as the protein content of media was very high and it caused a significant interference ( Figure 6A).…”
Section: Resultssupporting
confidence: 88%
“…As one can resolve from the images in Figure (see also Figure S5 in the Supporting Information), all white spots are localized outside cell membranes, while a granular shape of the corresponding blue spots in the SHG pattern suggests the aggregation of Si NPs in these regions. Such an aggregation in aqueous conditions via van der Waals forces was reported for many other nanoparticles (e.g., silica NPs) . It should be noted that SHG signals should be intense enough to detect only for large NP fragments (see our discussion below), confirming our supposition about the presence of large aggregations of Si NPs outside cell membranes.…”
supporting
confidence: 87%
“…Besides, it is worth noting that there is a possibility of the formation of a protein corona, since the samples were dispersed in serum-enriched DMEM. It common in the literature that the corona formed around the nanoparticles lowers its cytotoxicity [43,45,46,47] by lowering its positively-charged surface. …”
Section: Resultsmentioning
confidence: 99%